Frontispiece: Triangles and Squares for a Unique Molecular Crystal Structure: Unsupported Two‐Coordinate Lithium Cations and CC Agostic Interactions in Cyclopropyllithium Derivatives. Issue 7 (6th February 2018) - Dufrois, Quentin; Daran, Jean‐Claude; Vendier, Laure; Dinoi, Chiara; Etienne, Michel
Abstract : Organometallic Chemistry In their Communication onpage 1786 ff., M. Etienne et al. report a cyclopropyl lithium derivative that forms a tetramer in the solid state. The structure resembles the Cross of Occitanie.